Traditional investment research and social networks: Evidence from Facebook connections - Travis Dyer; Gerrit Köchling; Peter Limbach (University of Cologne, Centre for Financial Research (CFR), 2024)
We show that investors acquire more public information about firms to which they are more socially proximate. On average, a standard deviation increase in the Social Connectedness Index (Bailey et al., 2018) between a firm's headquarter county and a searcher county is associated with 30% more EDGAR filing downloads from the searcher county. The effect of social proximity on traditional investment research is distinct from the effect of geographic proximity. We find similar results studying headquarter relocations, investor-level data, and EDGAR downloads from European regions, for which physical distance should be irrelevant. Social proximity matters more during times of high market-wide uncertainty and for firms with weaker information environments. Finally, information gathered by socially proximate investors predicts short-term earnings and stock returns, but also heightened volatility. Collectively, the evidence indicates that social networks mitigate informational frictions and foster information acquisition in financial markets.
Keywords: D80; D83; G10; G41; M40; 330; Corporate disclosures; EDGAR; Geography; Information acquisition; Social networks; Social connections